2009
DOI: 10.1149/1.3223997
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrochemical Investigation of Anodic Polarization Behavior of CrS Inclusions in Stainless Steels

Abstract: The anodic dissolution behavior of CrS inclusions was compared with that of (Mn,Cr)S inclusions containing around 10 atom % Cr using a microelectrochemical cell in NaCl solutions. CrS inclusions were resistant to pit initiation compared with (Mn,Cr)S inclusions. The dissolution potential of CrS inclusions was in the transpassive region of stainless steels. Stable pits were initiated in this potential region. (Mn,Cr)S inclusions dissolved in the passive region of stainless steels, providing lower pitting potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 32 publications
3
53
0
Order By: Relevance
“…13 are in good agreement with the work of Muto et al, who demonstrated that the composition of (Mn,Cr)S inclusions changes, becoming Cr-rich under anodic polarization, and that oxide films form on the inclusions. 27 Lillard et al also observed Cu deposition on the MnS surface immersed in 0.1 M NaCl. 25 The results of the SEM/EDS analysis presented in Figs.…”
Section: Effect Of Electrode Size On Pit Initiation-comparison Ofmentioning
confidence: 91%
“…13 are in good agreement with the work of Muto et al, who demonstrated that the composition of (Mn,Cr)S inclusions changes, becoming Cr-rich under anodic polarization, and that oxide films form on the inclusions. 27 Lillard et al also observed Cu deposition on the MnS surface immersed in 0.1 M NaCl. 25 The results of the SEM/EDS analysis presented in Figs.…”
Section: Effect Of Electrode Size On Pit Initiation-comparison Ofmentioning
confidence: 91%
“…Figure 12 shows the microscopic polarization curves for the small areas of austenitic stainless steels with MnS, CrS, and Ti 4 C 2 S 2 inclusions in NaCl solutions at 298 K. The polarization curves for MnS and CrS were quoted from the literature. 20 As shown in this figure, the MnS inclusion dissolved in the passive region of stainless steels in 0.5 M NaCl, and pit initiation occurred. The CrS inclusion did not dissolve in the passive region of stainless steels, but pitting was initiated at the inclusion at higher potentials because of the transpassive dissolution of Cr-oxide film on the inclusion surface.…”
Section: Comparison Of Pit Initiation Resistance At the Inclusionsmentioning
confidence: 69%
“…The CrS inclusion did not dissolve in the passive region of stainless steels, but pitting was initiated at the inclusion at higher potentials because of the transpassive dissolution of Cr-oxide film on the inclusion surface. 20 In contrast, no pitting was observed at the Ti 4 C 2 S 2 inclusions even in 3 M NaCl. There is no current increase due to the inclusions dissolution and pitting in the polarization curve for the small area with the Ti 4 C 2 S 2 inclusions.…”
Section: Comparison Of Pit Initiation Resistance At the Inclusionsmentioning
confidence: 94%
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] After the anodic polarization (Fig. As many researchers have already pointed out, the current increase around 0.6 V is due to the anodic dissolution of MnS inclusions and stable pit initiation at the inclusions.…”
Section: Resultsmentioning
confidence: 93%